+0  
 
0
81
1
avatar

Let $f(x)$ be a quadratic polynomial such that $f(-4) = -22,$ $f(-1)=2$, and $f(2)=-1.$ Let $g(x) = f(x)^{16}.$ Find the sum of the coefficients of the terms in $g(x)$ that have even degree. (For example, the sum of the coefficients of the terms in $-7x^3 + 4x^2 + 10x - 5$ that have even degree is $(4) + (-5) = -1.$)

 Mar 22, 2020

Best Answer 

 #1
avatar+21017 
+1

A quadratic polynomial has the form:  f(x)  =  ax2 + bx + c

f(-4)  =  -22     --->     -22  =  a(-4)2 + b(-4) + c     --->     16a - 4b + c  =  -22

f(-1)  =  2        --->        2  =  a(-1)2 + b(-1) + c     --->         a -   b + c  =     2

f(2)  =  -1        --->       -1  =  a(2)2 + b(2) + c       --->       4a + 2b + c  =    -1

 

Combining the first equation with the third equation:

     16a - 4b + c  =  -22     --->                       16a - 4b +   c  =  -22            

       4a + 2b + c  =   -1     ---> x -4     --->     -16a - 8b - 4c  =    4

Adding down the columns:                                  -12b - 3c  =  -18     --->     4b + c   =  6

 

Combing the second equation with the third equation:

     a -   b + c  =    -2     --->     x -4     --->     -4a + 4b - 4c  =  -8

   4a + 2b + c  =   -1     --->                            4a + 2b +  c  =  -1

Adding down the columns:                                    6b - 3c  =  -9     --->     2b - c  =  -3

 

Combining these two new equations:        4b + c  =   6       

                                                                   2b - c   =  -3    

Adding down the columns:                         6b        =   3     --->     b  =  0.5

 

Substituting back:  c  =  4      and     a  =  -1.5     

 

You'll need to find the sum.

 Mar 23, 2020
 #1
avatar+21017 
+1
Best Answer

A quadratic polynomial has the form:  f(x)  =  ax2 + bx + c

f(-4)  =  -22     --->     -22  =  a(-4)2 + b(-4) + c     --->     16a - 4b + c  =  -22

f(-1)  =  2        --->        2  =  a(-1)2 + b(-1) + c     --->         a -   b + c  =     2

f(2)  =  -1        --->       -1  =  a(2)2 + b(2) + c       --->       4a + 2b + c  =    -1

 

Combining the first equation with the third equation:

     16a - 4b + c  =  -22     --->                       16a - 4b +   c  =  -22            

       4a + 2b + c  =   -1     ---> x -4     --->     -16a - 8b - 4c  =    4

Adding down the columns:                                  -12b - 3c  =  -18     --->     4b + c   =  6

 

Combing the second equation with the third equation:

     a -   b + c  =    -2     --->     x -4     --->     -4a + 4b - 4c  =  -8

   4a + 2b + c  =   -1     --->                            4a + 2b +  c  =  -1

Adding down the columns:                                    6b - 3c  =  -9     --->     2b - c  =  -3

 

Combining these two new equations:        4b + c  =   6       

                                                                   2b - c   =  -3    

Adding down the columns:                         6b        =   3     --->     b  =  0.5

 

Substituting back:  c  =  4      and     a  =  -1.5     

 

You'll need to find the sum.

geno3141 Mar 23, 2020

7 Online Users